Anthropometric measurements of Malaysian population for passenger cabin design of transport aircraft - Ahmad Habibillah, Nadia Hanani; Romli, Fairuz Izzuddin (Universiti Teknologi MARA, 2022)
In order to improve the passengers’ flying comfort, the aircraft cabin features should be ergonomically developed and designed. The key element for design ergonomics is the anthropometric measurements of the target users, which are vital in ensuring a good fit between their body characteristics and the resultant product or system design. Based on this notion, this study aims to establish the database for the measurement of body dimensions of the Malaysian population that is useful in design process of most cabin features. A total of 100 volunteers have participated in this study and their body dimensions are measured using standard measurement tools during a few conducted data collection sessions. Several standard anthropometric measurements of the Malaysian population for sitting and standing body postures have been derived from the descriptive statistics of the collected measurement data. They include stature, standing eye height, standing shoulder height, standing elbow height, standing hip breadth, standing shoulder breadth, sitting shoulder height, sitting elbow height, sitting eye height, sitting buttock-popliteal length and also sitting buttock-knee length. Furthermore, based on the comparison analysis with the referenced Malaysian anthropometric database, it can be concluded that the body characteristics of the Malaysian population are changing with time and the body measurements are expected to further increase in future. This means that the design sizing of the aircraft cabin features might need to be adjusted accordingly to be able to provide a comfortable flying experience for the future Malaysian passengers.